Modelling and Construction of Complex Shaped Polyvinyl Alcohol based Ultrasound Phantoms for Inverse Magnetomotive Ultrasound Imaging - Heim, Christian; Huber, Christian; Ermert, Helmut; Ullmann, Ingrid; Saleem, Taimur; Lyer, Stefan; Rupitsch, Stefan Johann (22. GMA/ITG-Fachtagung Sensoren und Messsysteme 2024, 2024)
With regard to the application in local cancer treatment, the inverse magnetomotive ultrasound (IMMUS) modality needs to be extended to 3D on complex shaped polyvinyl alcohol (PVA) phantoms. Our four basic construction elements can be combined step-by-step to manufacture such complex shaped phantoms. The construction of complex shaped ultrasound phantoms requires the four basic elements (i) molds, (ii) scattering material, (iii) layering process, and (iv) mechanical coupling between different parts of the phantom. In this contribution, we describe the construction elements in detail to show the trade-offs between the possible shapes and positioning of the encapsulated volumes and the production time. Furthermore, since IMMUS requires knowledge of the mechanical parameters and the geometry of the target tumorous tissue, these parameters have to be determined during a magnetic drug targeting (MDT) therapy. The insertion of MDT therapy relevant amount of superparamagnetic iron oxide nanoparticles (SPIONs) does not significantly change the material properties. Therefore, quantitative ultrasound-based tissue characterization techniques (UTCT) such as shear wave elastography (SWE) or transient elastography (TE) can be used to characterize the target tumorous tissue once in advance of an MDT therapy. In this contribution, SWE and TE are exploited to determine shear wave velocity in PVA phantoms. Both methods show promising results for the determination of Young's modulu
Keywords: Magnetic Drug Targeting; Magnetic Nanoparticles; Magnetomotive Ultrasound Imaging; Polyvinyl Alcohol Ultrasound Phantom; Ultrasound-based Material Characterization